Location based BRAF V600E mutation status and dimension patterns of sporadic thyroid nodules: a population-based study - Hui Tang; Dan Guo; Bin Yang; Shu-hua Huang (BMC Cancer)
Abstract Fine-Needle Aspiration (FNA) has been routinely used for papillary thyroid carcinoma (PTC) diagnosis. One single liquid based tissue sample collected from FNA can be used for both cytological diagnosis and genetic testing at the same time. BRAF V600E mutation exhibits 100% specificity and high sensitivity for papillary thyroid carcinoma (PTC). However, FNA based studies on the genotypic (BRAF V600E) and ultrasonic (US) imaging characteristics (location and diameter) are exceedingly rare. Here, we aimed to study the genotypic (BRAF V600E) and US imaging characteristics (location and diameter) in a large retrospective cohort. A total of 4808 patients with thyroid nodules from a tertiary center underwent FNA, and 2430 patients underwent molecular testing. Our data demonstrated that the thyroid nodules were predominantly located on the right side (p = 0.0004). Patients diagnosed with Bethesda VI cytology had significantly more right-sided thyroid nodules (p = 0.0041). Interestingly, among patients with PTC with lymph node metastasis (LNM), right-side-affected LNM was significantly more common than left-side-affected LNM, which implies a biased regional LNM of right-side-located thyroid nodules (p = 0.0007). The size of BRAF-V600E mutated or right-lobe located nodules was significantly larger than that in the control group (p = 0.0156), and patients with a BRAF V600E mutation were considerably younger than those with wild-type BRAF.